EMERGING ORGANIZATIONAL CULTURE FROM THE BENEFITS AND DRAWBACKS OF FACEBOOK MESSENGER GROUP CHAT TREND IN PUBLIC SCHOOLS - Salazar, Catherine Aragon (Universitas Brawijaya, Indonesia, 2022)
The new normal in education leads to new normal practices among teachers in public schools to carry out the Department of Education Basic Education Learning Continuity Plan (BE- LCP), leading to the Facebook Messenger group chat trend in public schools. This study explores the benefits and drawbacks of this communication application as experienced by public-school teachers and aimed at understanding patterns of emerging organizational culture due to the utilization of Facebook Messenger group chats. The study utilized the phenomenological research design. Data were gathered through semi-structured one-on-one interviews and focus group discussions with randomly selected public-school teachers, and results were interpreted through thematic analysis. The study found out that the Facebook Messenger group chat trend is beneficial in convenience, accessibility, and learning delivery while its drawbacks are work-life balance, emotional-psychological, and technical. Open communication, sensitive communication, netiquette in social behavior, and technological reliance were the patterns of organizational culture emerging from using Facebook Messenger group chats. Assessment on the appropriateness of its use depending on the purpose and further innovation on its features that may fit well for its use in education and work purposes were recommended to manage its drawbacks and optimize its use in the new normal education delivery.